[Rezension von: Malherbe, Abraham J., 1930-2012, Light from the Gentiles : hellenistic philosophy and early Christianity : collected essays, 1959-2012] - Schmeller, Thomas (Biblische Zeitschrift, 2015)
"Light from the Gentiles: Hellenistic Philosophy and Early Christianity" published on 24 Nov 2015 by Brill | Schöningh.